2018
DOI: 10.1097/md.0000000000010970
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pedicle screw placement comparing robot-assisted technology and the free-hand with fluoroscopy-guided method in spine surgery

Abstract: There are significant differences in accuracy between RA surgery and FH surgery. It was demonstrated that the RA technique is superior to the conventional method in terms of the accuracy of pedicle screw placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
131
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 23 publications
1
131
0
Order By: Relevance
“…In a meta-analysis by Fan et al [16], robot-assisted pedicle screws were significantly more accurate than the conventional freehand with fluoroscopy-guided method. After comparing the accuracies of 1255 pedicle screws in the freehand group to 1682 pedicle screws in the robot-assisted group, it was concluded that the robot-assisted technique was superior to the conventional method in terms of pedicle screw accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis by Fan et al [16], robot-assisted pedicle screws were significantly more accurate than the conventional freehand with fluoroscopy-guided method. After comparing the accuracies of 1255 pedicle screws in the freehand group to 1682 pedicle screws in the robot-assisted group, it was concluded that the robot-assisted technique was superior to the conventional method in terms of pedicle screw accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was not a comparative study, but rather an exploratory study on the effectiveness of navigated robotic assistance in posterior screw placement. Multiple studies have examined the screw accuracy of robot-assisted screws versus freehand screw placement with fluoroscopy guidance and found improved screw accuracy, lower radiation, improved outcomes, and fewer revisions from screw malposition with navigated robotic assistance [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis focusing on the comparison of the accuracies of robot‐assisted and free‐hand pedicle screws insertion, 10 studies were included and analyzed. The study showed that the robot‐assisted technique is more accurate than the conventional method after analyzing the incidences of “perfect” and “clinical acceptable” pedicle screw insertions.…”
Section: Introductionmentioning
confidence: 99%
“…This was also reflected on the length of stay of patients operated with the use of robotic surgery: in fact, Hyun et al 28 showed an average length of stay of 9.4 days for FH procedures vs. 6.8 days for robotic surgical procedures. Likewise, Fan et al 80 demonstrated a decrease of number in postoperative days from 6.3 ± 1.2 in the RAN group vs. 8.9 ± 1.8 in the FH group.…”
Section: Discussionmentioning
confidence: 87%
“…79 Moreover, robotic spine surgery gives the possibility to operate with a lower risk of neurovascular damage if compared to FH approaches, thanks to the use of motors and stabilizers. 80 As far as the reoperation rate is concerned, Kantelhardt et al 81 demonstrated that only 1% of robotic procedures (including both percutaneous and open approaches) needed revision surgery, compared to the 12.2% reoperation rate showed for conventional procedures. Moreover, the study reported postoperative infections in 2.7% of the patients undergoing robot-guided procedures compared to 10.7% in open nonrobotic ones.…”
Section: Discussionmentioning
confidence: 99%